Associations Between Serum 25-Hydroxyvitamin D Levels and Thyroid Function Parameters in Previously Healthy Children Aged 6 to 24 Months - Guo Y; Wu CY; Deng YH; Wu JL (Dove Medical Press, 2020)
Yong Guo, Chun-Yan Wu, Yu-Hong Deng, Jie-Ling Wu Department of Children’s Health Care, Guangdong Women and Children Hospital, Guangzhou Medical University, Guangzhou 511400, People’s Republic of ChinaCorrespondence: Jie-Ling WuDepartment of Children’s Health Care, Guangdong Women and Children Hospital, Guangzhou Medical University, Guangzhou 511400, People’s Republic of ChinaTel +86 2039151521Email jieling3861@163.comPurpose: Vitamin D deficiency has been linked to overt thyroid diseases. Data on the effects of vitamin D status on thyroid function in children are less examined. The goal of the present study was to explore the association between serum 25-hydroxyvitamin D [25(OH)D] levels and thyroid function parameters in early childhood.Patients and Methods: This was a cross-sectional study involving record-linkage of children’s data of routine health check-ups for promoting early childhood development at Guangdong Women and Children’s Hospital; 2869 children aged 6– 24 months were included from January 2015 to May 2017. Serum 25(OH)D, thyroid stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) levels were measured using the electrochemiluminescence immunoassay.Results: The study population had a mean serum 25(OH)D level of 79.7 ± 28.1 nmol/L and 12.5% vitamin D deficiency and 36.0% insufficiency rates. The rates of thyroid dysfunctions detected were 2.9% hypothyroidism, 4.2% subclinical hypothyroidism, 0.9% hyperthyroidism, and 1.7% subclinical hyperthyroidism among the previously healthy children aged 6 to 24 months. Serum 25(OH)D levels had no significant correlation with TSH (r = 0.022, P = 0.236), FT3 (r = 0.014, P = 0.440) and FT4 (r = − 0.059, P = 0.056) levels. No significant difference in the levels of thyroid hormones was found between the different quartiles of 25(OH)D level. Vitamin D deficiency [25(OH)D < 50 nmol/L] was associated with hypothyroidism (adjusted odds ratio = 2.16, 95% confidence interval: 1.18– 3.94) but not with subclinical hypothyroidism, hyperthyroidism, and subclinical hyperthyroidism.Conclusion: Vitamin D deficiency is slightly associated with hypothyroidism. No associations were found between serum 25(OH)D levels and thyroid-related measures (TSH, FT3, and FT4) in previously healthy children aged 6– 24 months.Keywords: thyroid stimulating hormone, free triiodothyronine, free thyroxine